Death in the house - Berkeley, Anthony, 1893-1971 (House of Stratus, 2001)
When Lord Wellacombe, the Secretary of State for India, collapses in the House of Commons and dies everyone suspects a stroke. His death causes political waves as a successor is sought and there is the question of a bill to be put through. But then tests show Wellacombe to have been poisoned and not by any conventional method - a thorn covered in South American poison is discovered under the dead man's coat collar. Is this the work of an international terrorist or someone closer to home? "REVIEW: 'Anthony Berkeley is the supreme master not of the "twist" but of the "double-twist"' (The Sunday Times) AUTHBIO: A journalist as well as a novelist, Anthony Berkeley was a founding member of the Detection Club and one of crime fiction's greatest innovators. He was one of the first to predict the development of the 'psychological' crime novel and he sometimes wrote under the pseudonym of Francis Iles. He wrote twenty-four novels, ten of which feature his amateur detective, Roger Sheringham